Peran Satgas PPKS terhadap Pelecehan Seksual di Perguruan Tinggi dan Upaya Pencegahanya - Ardelia Citra Febriyanti; Diah Gustiniati Maulani; Maya Shafira; Erna Dewi; Aisyah Muda Cemerlang (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research is motivated by the increasing cases of sexual harassment in the university environment which has a serious impact on the psychological condition of victims and the academic climate as a whole. Universities that are supposed to be safe spaces for learning and development are often places where serious violations of human dignity occur. The establishment of the Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS) is an important step by the government to provide protection, assistance, and a more structured complaint mechanism for victims of sexual violence. This study aims to examine the criminal acts of sexual harassment in universities as well as analyze the role and countermeasures carried out by the PPKS Task Force in handling these cases. The research methods used are normative juridical approaches and empirical juridical approaches. The normative approach is carried out by analyzing relevant laws and regulations, such as the Sexual Violence Crime Law and university regulations related to the prevention of sexual violence. Meanwhile, an empirical approach is carried out through observation and analysis of the implementation of the tasks of the PPKS Task Force in the campus environment. The results of the study show that the PPKS Task Force plays a significant role in providing psychosocial support for victims, conducting socialization related to the prevention of sexual violence, and enforcing anti-sexual violence policies in universities. In addition, the PPKS Task Force also implements various programs such as gender awareness training, legal assistance, and building a complaint system that is more accessible to students. The implications of this study confirm the importance of education and increasing awareness among the academic community regarding the issue of sexual harassment.